2022
DOI: 10.1155/2022/4259499
|View full text |Cite|
|
Sign up to set email alerts
|

Epidural Anesthesia versus General Anesthesia for Total Knee Arthroplasty: Influences on Perioperative Cognitive Function and Deep Vein Thrombosis

Abstract: Purpose. This research mainly discussed the impacts of epidural anesthesia (EA) and general anesthesia (GA) on perioperative cognitive function (CF) and deep vein thrombosis (DVT) in patients undergoing total knee arthroplasty (TKA). Methods. One hundred and twenty-four patients undergoing TKA in our hospital between July 2015 and October 2021 were selected, of which 74 patients received EA (research group) and the other 50 patients received GA (control group). Perioperative CF, DVT, stress response indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%